The Costs of Occupational Accidents and Occupational Diseases on Country Economies: The Case of Türkiye - Mustafa Özdemir (Cuestiones de Fisioterapia, 2025)
Due to occupational accidents and occupational diseases, in addition to social costs, there are visibleeconomic costs that can be calculated, and indirect economic costs are known as the invisible partof the iceberg. Indirect or hidden costs are considered eight times higher than visible economiccosts. This study analyses the official data in the Social Security Institution (SGK) statisticalyearbooks on occupational accidents and diseases occurring in Turkey in the six years between 2017and 2022. The situation of occupational accidents and occupational diseases in Turkey and thefinancial burden on the national economy are tried to be calculated. It aims to contribute to thepolicies on this issue by making suggestions.